Obtención de biodiesel a partir del efluente generado durante el proceso de extracción de aceite crudo de palma - Duffey Castillo, Nancy Sofía (2022)
In the present investigation, the effluent generated during the crude palm oil extraction process (POME), a waste that has been little or not studied at all, was studied. Therefore, the objective of the present research was to obtain biodiesel from the effluent generated during the crude palm oil extraction process, for which the POME was collected from the OLEOCASTILLO company, located in the city of Santo Domingo, a physical and chemical analysis was performed in the research laboratories of the State University of Bolivar, where it was identified that it contained a high percentage of free fatty acids (51.23%), so a previous esterification was performed with methanol (10: 1) and sulfuric acid (1%) to reduce its free fatty acid content to 2% so that the transesterification reaction could be carried out. To obtain biodiesel, a DCA experimental design was applied, in AxB factorial arrangement (3x2) with three repetitions, using the molar ratio of (6:1, 9:1, 12:1), and percentage of catalyst (0.1; 1.0%), showing that a higher yield is obtained with the ratio alcohol: oil 6:1 and 0.6% of catalyst, which corresponds to treatment 1 (a_1 b_1), obtaining a 79% yield. The biodiesel obtained was analyzed according to INEN 2482, and it was found that it complies with the characteristics to be considered a biofuel.